Carbon nitride nanowires/nanofibers: A novel template-free synthesis from a cyanuric chloride–melamine precursor towards enhanced adsorption and visible-light photocatalytic performance. Issue 3 (15th February 2016) - Xie, Meng; Wei, Wei; Jiang, Zhifeng; Xu, Yuanguo; Xie, Jimin
Abstract: The development of a graphitic carbon nitride (g-C3 N4 ) photocatalyst is of great importance to a variety of visible utilization application fields. The desired high efficiency can be achieved by employing well-controlled g-C3 N4 nanostructures. In this study, we successfully synthesized high surface area g-C3 N4 nanowires and nanofibers using a cyanuric chloride and melamine precursor dispersed in a solvothermal reaction and with a subsequent calcination step. The obtained novel nanowire product had a diameter of 10–20 nm and a length of several hundreds of nanometers, while the nanofibers revealed fibrous nanostructures of randomly dispersed fibers with an average diameter of ~15 nm. The adsorption and photocatalytic experimental results indicated that the as-prepared nanowires and nanofibers showed enhanced activities compared with bulk g-C3 N4 . Based on our experimental results, a possible photocatalytic mechanism with hydroxyl and superoxide radical species as the main active species in photocatalysis was proposed. Moreover, our strategy may provide progress toward the design and practical application of 1D g-C3 N4 nanostructures in the adsorption and photocatalytic degradation of pollutants.